Caracterización física, química y biológica de las aguas de los ríos Huallaga, Paranapura y Shanusi en el ámbito correspondiente a la ciudad de Yurimaguas. Loreto - Armas Napuchi, Jackie (2010)
In this work, the physical, chemical and biological water Huallaga, and Shanusi Paranapura rivers in the corresponding Yurimaguas field conditions and variations and relationship were discussed during the months of rains and droughts. Besides the physical, chemical and biological water main collectors Yurimaguas conditions and their variations and relationships and analyzed; Finally the spatial distribution of varying concentrations for stations and times, the physical, chemical and biological parameters of water from the Huallaga rivers Shanusi Paranapura and determined. 5 monitoring of surface water was conducted in a six (6) months falling between the months of March to August 2009 and four (4) monitoring of waters of the four (4) main sewers of the city (Atun ravine Quebrada Zamora, Quebrada Aguamiro and Quedada. Michuyacu) in the month of December 2009 . the river water were sampled on the basis of 20 parameters (pH, temperature, turbidity, dissolved oxygen, conductivity, total dissolved solids, arsenic, copper, Cadmium, Chromium, Iron, Manganese, Mercury, Lead, Zinc, Oils Fats, TPH, fecal coliforms, total coliforms and E. coli). The values ​​obtained in the laboratory were compared with Environmental Quality Standards for Water (ECAS) approved by Supreme Decree No. 002-2008-MINAM and according to the classification to which each belongs river according to Resolucióriacion Jefatural No. 0291-ANA-2009., was applied and the analysis of variance and correlation analysis. The spatial distribution of varying concentrations for stations and times, was made on the basis of 6 parameters: temperature, pH, turbidity, manganese, iron and fecal coliform, which presented themselves highly variable by season and time values​​. Result was obtained as detailed below: Physical, chemical and biological water the Huallaga rivers Shanusi Paranapura and characterization must Paranapura the average dry season turbidity exceeds the limit value (100 NTU) in ECAS established for Class I, Sub category A2 , with a value of 434 NTU and 463.33 UNT, at stations 17 and 18, respectively; while in rainy season the average concentration of Fierro registered Huallaga river Shanusi Paranapura and was 2.4 mg / L, 2.4 mg / L and 2.613 mg / L and in dry season was 3.14 mg / L, 20.59 mg / L and 6.34 mg / L, exceeding the limit (0.3 mg / l) in the Ecuadorian standard established for the case of Shanusi and Huallaga River and the ECAS for Paranapura case. On the other hand, the average concentration of manganese registered Huallaga river in the rainy season was 0.217 mg / L, exceeding the limit value set in the Standard Ecuadorian (0.1 mg / L) and 0.269 mg / L, 0.434 mg / L and 4.876 mg / L in the dry season and Shanusi, Huallaga and Paranapura respectively rivers; exceeding the permissible limits for the Standard Ecuadorian case of the first two mentioned rivers and ECAS for Paranapura whose limit is 0.4 mg / L. Copper (Cu) exceeds the limit value set in the ECAS with a value of 0.021 mg / L and 0.022 mg / L at stations 5 and 16, respectively. The concentration of fecal coliform that exceed the permissible limits set (4,000 MPN / 100mL) established in Resolution Jefatural both rainy and dry season were: 3, 4, 10, 12, 16,17 and 18; with values ​​and 8165.47025 5432.5 and 81400, 10475 and 12866.67, 10800 and 13966.67, 5766.67 and 7550, 12400 and 18050, 4943.33 and 5665, respectively. Physical chemical and biological characterization of the main water collectors was obtained that the Dissolved Oxygen (DO) - Atun Quebrada (0.5 ppm), Qda. Aguamiro (0.52 ppm), Qda. Zamora (0.67 ppm) and Qda. Mishuyacu (2.99 ppm) -; Turbidity (NTU) - Atun Quebrada (137.72 NTU), Qda. Aguamiro (112.5 NTU) -; Cadmium (Cd) - Mishuyacu (0.13mg / L) -; Total Petroleum Hydrocarbons (TPH) - Atun gorge (0.237 mg / L) and Zamomora (0.57 mg / L) -; Manganese (Mn) -Tuna gorge (0.44mg / L), Zamora (0.14 mg / L) and Mishuyacu (0.31 mg / L); Lead (Pb) - Zamora (0.031 mg / L) and Mishuyacu (0.037mg /); Oils and Fats (A and G)-in all 4 seasons (2.87mg / L, 5.2 mg / L, 15.53 mg / L, 2.47 mg / L) -; Iron (Fe) - in all seasons (7.10 mg / L, 2.16 mg / L, 2.28 mg / L, 9.98 mg / L) -; Fecal Coliform - in all seasons (1.17x108NMP / 100ml, 4.2x108NMP / 100ml, 8.28x107NMP / 100ml and 8.4x107 MPN / 100ml) -; Total Coliforms - in all seasons (3.35x107NMP / 100ml, 4.02x108NMP / 100ml, 4.7x107NMP / 100ml and 1.14x107NMP / 100ml) and; Finally, E. Coli.- the creek and Aguamiro Atun (2.06x107 MPN / 100ml and 4.02x108 MPN / 100ml), exceeded the maximum permissible limits.